C-ARM GUIDED COELIAC PLEXUS BLOCK FOR MALIGNANT NEOPLASTIC LESION OF SUPRARENAL GLAND - DR. SHIVANAND LK,; DR.PRATIBHA S.D,; DR. VIDYA A.PATIL, (International Journal of Pharma and Bio Sciences, 2015)
A 65 year old female presented with pain abdomen and was diagnosed to be having a malignant suprarenal gland tumour . Patient was not relieved of pain with conservative management, therefore coeliac plexus block under C- ARM guidance was planned.Coeliac plexus blockade with local anaesthetic (LA) was introduced as early as in 1914.1 Indications for coeliac block- Abdominal pain of neoplastic/non malignant origin, Acute pain secondary to arterial embolisation of the liver (cancer therapy), Neurolysis of coeliac plexus to palliate pain of retroperitonium/upper abdominal malignancy. Diagnostic coeliac plexus block given with 15 ml 0.5% bupivacaine under C-ARM guidance and patient was relieved from pain for two days. Later therapeutic block was given with 20 ml of 50% of absolute alcohol on each side under C-ARM guidance. Patient was relieved from pain and followed up for one week and discharged satisfactorily. Conclusion: Coeliac plexus block can be used as a sole pain relief technique for suprarenal gland malignant tumour